(169) Economic Conditions of Vertical Expansion in The U.A.R. Agriculture(P2) - hammam, ezz el din (the institute of national planning, 2018)
in the previous paper 1 i have tried to give a brief idea about agriculture in the U.A.R. at various stages within the period of the last twenty years. mention was made to condition which existed in agriculture before 1952, measures which were taken by the revolutionary.